The lived experiences of directors providing leadership to part-time faculty at study abroad centers in Italy: a phenomenological analysis - Earhart, Alan, author; Gloeckner, Gene, advisor; Kuk, Linda, advisor; Lynham, Susan, committee member; Sample, Pat, committee member (Colorado State University. Libraries, 2021)
In the 2017-2018 academic year, 332,727 U.S. university students participated in a study abroad program in a foreign country (Institute of International Education, 2018). Many of these students attend courses taught by part-time faculty, hired locally by study abroad centers with affiliations to U.S. universities. The directors of these centers have responsibility for all aspects of the study abroad programs, including academics and the faculty. The purpose of this interpretative phenomenological analysis (IPA) study was to investigate how directors of study abroad centers in Italy understand and experience their leadership of part-time faculty. The main research question asked how directors of study abroad centers in Italy understand and experience their leadership of the part-time faculty they supervise? Eight individuals shared their experiences through semi-structured interviews and a follow-up focus group. The participants' essential experience in providing leadership to part-time faculty at study abroad centers in Italy was bridging the gap between different realities. The unique research setting produced results showing that participants employed some practices supporting part-time faculty not found in past research on leading part-time faculty. These included: paying for travel to academic conferences, hosting academic conferences organized by PT faculty, and paying to publish PT faculty scholarship.